The Needs Deficit of Pre-Release Juvenile Offenders to be Re-Integrated into the Educational System - Zainol, Intan Nooraini Haji; Azman, Azlinda; Yusof, Masarah Mohamad; Bahrin, Farhana Kamarul; Shaed, Maslina Mohammed (International Journal of Asian Social Science, 2018)
This paper discusses the needs deficit of pre-release juvenile offenders from the educational perspectives, which might complicate their chances for successful re-integration after release. This qualitative study involved a total of 17 pre-release juvenile offenders who have been selected using the purposive sampling technique from three correctional institutions in Kuala Lumpur, Malaysia. Data were gathered through in-depth interviews and analysed using content analysis technique. The study findings have indicated that many of the respondents have major concerns about their history of disciplinary problems, for being dropped-out from schools, and having low academic abilities, which they perceived as primary hindrances for them to be re-enroll in schools due to stigma, discrimination and rejection from the authorities. Some respondents believed they might face struggle in the learning process even if they get re-enrolled because the need to catch up with the syllabus that they have missed since they have been out of school for quite some time. These deficits become major challenges for them to acquire better education and qualification, hence it can affect their opportunity for a more stable job in the long run. This paper also discusses several intervention strategies to improve the access, quality and implementation of academic programme and to strengthen the re-integration support through close collaboration, partnership and commitment from the Ministry of Women, Family and Community Development (MWFCD); the Department of Social Welfare (DSW); Ministry of Education (MOE) and other relevant stakeholders in assisting these juvenile offenders in meeting with their educational needs, which all these are in line with the Convention on the Rights of the Child (CRC) and National Child Policy.